2010
DOI: 10.1111/j.1742-7843.2010.00541.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Toxicology of Dental Composite Resin Extracts in Somatic Cells In Vivo

Abstract: The aim of this study was to assess the potential genetic toxicity associated to nine aqueous extracts from dental composite resins (Charisma, Fill Magic, Fill Magic Flow, Durafill, TPH Spectrum, Concept, Natural Look, Filtek Z250 and Filtek P60) and one random extract. Homologous mitotic recombination, point and chromosomal mutation effects were determined in somatic proliferative cells of Drosophila melanogaster exposed to aqueous extracts of the clinically used composites. Reproducible increases in clone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
7
0
2
Order By: Relevance
“…After 6 h of exposure, a relevant number of double-strand breaks in human gingival fibroblasts was detected at a UDMA concentration of 14.12 μg mL -1 [84]. These genotoxic effects were confirmed in vivo using eluates of UDMA-and/or TEGDMA-based composites [86]. By contrast, an older study by Schweikl et al [88] found only a slight increase of micronuclei compared with the control group after exposure to UDMA.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…After 6 h of exposure, a relevant number of double-strand breaks in human gingival fibroblasts was detected at a UDMA concentration of 14.12 μg mL -1 [84]. These genotoxic effects were confirmed in vivo using eluates of UDMA-and/or TEGDMA-based composites [86]. By contrast, an older study by Schweikl et al [88] found only a slight increase of micronuclei compared with the control group after exposure to UDMA.…”
Section: Discussionmentioning
confidence: 88%
“…Even in large temporary restorations, these concentrations are not to be expected. By contrast, UDMA exhibits a mutagenic effect that is more potent by a factor of 1.6 [86,87]. Using a comet assay with human parotid gland cells and lymphocytes, initial DNA damage was observed after only 60 min of exposure at a UDMA concentration of 0.047 μg mL -1 [75,76].…”
Section: Discussionmentioning
confidence: 95%
“…Unpolymerized resin monomers can be leached into dental pulp tissue as high as several millimolars in concentration even without pulpal exposure in the tooth cavity . The exposure level of resin monomers to dental pulp tissue will be dependent on the thickness of remaining dentin in the tooth cavity .…”
mentioning
confidence: 99%
“…The mechanistic basis underlying the genotoxicity of urethane dimethacrylate (UDMA) and TEGDMA is related to homologous recombination and gene/chromosomal mutation (28). BISGMA and 2-hydroxyethyl methacrylate (HEMA) had no statistically significant effect on genetic apparatus (29,30). Conversely, both compounds exhibited genotoxicity in V79 cells detected by comet assay and micronucleus test (15,30).…”
Section: Dental Restorative Materials and Related Compoundsmentioning
confidence: 99%